2021
DOI: 10.30798/makuiibf.805133
|View full text |Cite
|
Sign up to set email alerts
|

Alienation to Academicianship During the Covid-19 Pandemic

Abstract: Bu çalışmanın amacı, pandemi döneminde yaşanan kaygı ve sosyal izolasyonun akademisyenlerin mesleklerine olan yabancılaşma düzeylerine etkisini ve psikolojik olarak güçlü olmanın akademik yabancılaşmayı azaltıcı etkisini araştırmaktır. Bunun yanında akademik performans ile akademisyenliğe yabancılaşma ve psikolojik dayanıklılık ilişkisi de incelenmiştir. Araştırmanın katılımcılarını, Türkiye’nin 75 ilinden 684 akademisyen oluşturmaktadır. Araştırma verileri online anket tekniği ile toplanmıştır. Veriler üzerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…cause alienation in academics. These result in a decrease in creativity, scientific research, commitment to work and cooperation with colleagues and productivity (Alparslan, Polatci & Yastioglu, 2021). Obligation to continue education remotely during the Covid-19 pandemic and the uncertainty about the next academic year brought along some problems.…”
Section: Academic Staff and The Consept Of Alienationmentioning
confidence: 99%
“…cause alienation in academics. These result in a decrease in creativity, scientific research, commitment to work and cooperation with colleagues and productivity (Alparslan, Polatci & Yastioglu, 2021). Obligation to continue education remotely during the Covid-19 pandemic and the uncertainty about the next academic year brought along some problems.…”
Section: Academic Staff and The Consept Of Alienationmentioning
confidence: 99%
“…It can be assumed that the ongoing changes caused by the Covid-19 virus in the education system have increased the marginalization and exhaustion of the teacher organization (Alparslan et al, 2021). While distance education has been a popular learning experience for years, the global need to digitize education has never been greater.…”
Section: Pandemic and Burnoutmentioning
confidence: 99%
“…It is seen that there are studies on alienation in the literature (Seeman, 1959;Feuer, 1962;Banai, Reisel and Probst, 2004;Nair and Vohra, 2009;Yılmaz and Sarpkaya, 2009;Güzel and Kirazoğlu, 2019;Kopuz and İşci, 2020;Mizrahi, 2020;Yurdakul and Öneren, 2020;Çiçek and Türkmenoğlu, 2020). In addition, it has been observed that there are studies on alienation in higher education institutions (Turhan, 2007;Yıldız and Alıcı, 2019;İrdem, 2021), and it is noteworthy that there are almost no studies on alienation from work during the pandemic process (Alparslan, Polatcı and Yastıoğlu, 2021). It is thought that the effects of the radical changes in the pandemic process on individuals trying to keep up with the speed of the globalizing world and struggling with various behavioral problems are neglected in terms of alienation from work in fact, at a time when there are suitable conditions for its emergence.…”
Section: Summary Introductionmentioning
confidence: 99%